Center of Pressure Velocity and Dynamic Postural Control Strategies Vary During Y-Balance and Star Excursion Balance Testing - Kristen L Jagger; Brent Harper (North American Sports Medicine Institute, 2024)
# Background Dynamic postural control (DPC) describes an individual's ability to maintain balance within their base of support in both anticipatory and reactive balance situations and has been measured using center of pressure (COP) velocity. Common standardized DPC assessments for active adults include the modified Star Excursion Balance Test (MSEBT) and the Y-Balance Test (YBT). # Hypothesis/Purpose The purpose of this study was to explore DPC during performance of the MSEBT, the YBT, and a modified version of the YBT, the MYBT. It was hypothesized that feedback from the YBT/MYBT reach indicator would enhance DPC. # Study Design Cross-sectional study # Methods Twenty-one participants (9 females, 12 males, mean age 24.5±1.2 years) performed three trials in each direction (anterior-AN, posteromedial-PM, and posterolateral-PL) on each balance test during one session. The YBT frame was placed atop a force plate for all testing. Frontal and sagittal plane COP velocities (COPx and COPy, respectively) were recorded throughout each trial and resultant COP (COPr) velocities were calculated. # Results Significant main effects were present for test (*F*=4.485, *p*\<0.001) and reach direction (*F*=61.594, *p*\<0.001). Post hoc analyses for test indicated significant differences in COPy between YBT and MSEBT (*p*=0.034) and between MYBT and MSEBT (*p*\<0.001), as well as significant differences in COPr between MYBT and MSEBT (*p*=0.002). Post hoc analyses for reach direction revealed significant differences in COPx between AN and both PM (*p*\<0.001) and PL (*p*\<0.001) directions, in COPy between AN and PM (*p*\<0.001) and PL (*p*\<0.001) directions, and COPr between AN and PL (*p*=0.043) directions only. # Conclusion External proprioceptive feedback from the reach indicator improved DPC during the YBT and MYBT when compared to the MSEBT. Sagittal plane COP velocities were reduced when external proprioceptive feedback from the reach indicator was present, while frontal plane COP velocities were not affected in this group of participants. # Level of Evidence 2b